EFEKTIVITAS PENGGUNAAN BUS TRANS PATRIOT SEBAGAI ANGKUTAN UMUM MASSAL DALAM MENGATASI KEMACETAN DI KOTA BEKASI - Indah Aurellia Putri Sahara; Asep Hidayat; Wawan Setiawan Abdillah (Jurnal Inovasi Penelitian, 2022)
Congestion is a situation or atraffic choke due to the large number of vehicles that exceed the capacity of the road. Congestion problems become multidimensional problems that interfere with activities. The results of the government's performance in serving the community can be seen in public services that become benchmarks. Good government performance can result in good quality public services. Successful public services are built by the government by looking at professionalism, effectiveness and efficiency. This research uses descriptive qualitative research methods using interview data collection techniques, observations and documentation. The results of this study show that the use of Trans Patriot buses has not been effective to reduce congestion, then it still often intersects with angkot, the socialization process is lacking and in the implementation of the Trans Patriot bus program can be said to have not been able to reduce congestion due to the lack of a fleet of buses operating.